Features of phase and structure formation in obtaining high-entropy alloy of Fe-Ti-Cr-Mn-Si-C system from a powder mixture of ferroalloys - Bagliuk, G.A.; Marych, M.V.; Shishkina, Yu.O.; Mamonova, A.A.; Gripachevsky, O.M.; Kyryliuk, S.F. (Physics and Chemistry of Solid State, 2022)
The peculiarities of the structure and phase composition of the high-entropy alloy of the TiCrFeMnSiC system obtained from the powder mixture of ferrotitanium, ferrochrome and ferrosilicon-manganese ferroalloys are considered in the work. The technological scheme of alloy production included joint grinding of the mixture in a planetary mill, consolidation of the blanks, their heating to 1100 0C, hot forging on the arc press and subsequent annealing of hot-forged samples at 1200 0C. According to the results of X-ray analysis of the obtained alloy, it was found that the main phase of the alloy is the BCC phase with the parameter of the cubic lattice a = 0.2868 nm, which is a solid solution based on alloying components of the original charge. The phase composition of the composite also recorded titanium carbide TiC with FCC lattice with the parameter a = 0.4319 nm, which corresponds to a stoichiometric composition of about TiC0.6 and a small amount of FCC phase of iron-chromium carbide (Cr, Fe)23C6 with lattice parameter a = 1.0645 nm. The material has a high hardness (up to 60-61 HRC), which can provide high resistance of this multicomponent alloy.